2011
DOI: 10.1103/physreve.84.041802
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-induced entropic depletion potential

Abstract: We study the effective interactions between nanoparticles immersed in an athermal polymer solution using Molecular dynamics. The directly measured polymer-induced depletion forces are well described with a scaling model in which the attraction between particles is caused by the depletion of concentration blobs and thus independent of the length of the polymer chains. We find strong evidence for a repulsive barrier which arises when the distance between the particles is of the order of the correlation length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 29 publications
(35 reference statements)
9
45
0
Order By: Relevance
“…This explanation is also supported by the findings of Cao et al, who found attractive interactions between hypothetic colloids at low‐polymer concentrations and repulsive interactions at high‐polymer concentrations by molecular dynamic simulation (MD simulation) .…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…This explanation is also supported by the findings of Cao et al, who found attractive interactions between hypothetic colloids at low‐polymer concentrations and repulsive interactions at high‐polymer concentrations by molecular dynamic simulation (MD simulation) .…”
Section: Introductionsupporting
confidence: 76%
“…As described in the introduction section, no repulsive forces are present at high polymer concentrations, as shown by Kozer et al with dynamic light scattering experiments and by Cao et al using molecular‐dynamic (MD) simulations . Cao et al estimated a potential for the interactions of two colloids in aqueous solution caused by a polymer. These calculations of Cao et al were used within this work to estimate a function for W PRISMmod shown in Eq.…”
Section: Modelling B22 Data Using the Mxdlvo Modelmentioning
confidence: 91%
See 1 more Smart Citation
“…For polymers in the swollen (dilute) regime, one would expect that the thickness of the depletion layer around the colloids is close to R g and that the range of the depletion interaction for our system is ∼2R g = 12σ m = 0.6σ c . [1,125] This would correspond to a range of the attractive depletion well which is in excess of the threshold value (∼σ c /5), below which the colloidal liquid phase is expected to become metastable relative to the solid [124]. However, since the effective polymer packing fraction corresponds to the crossover (or semi-dilute) region between swollen chains and the melt, the range of the depletion interaction is determined not by R g but, rather, by a correlation length ξ , often referred to as the blob size of the polymer [33,[125][126][127].…”
Section: Studies Of the Separate Polymer-rich And Colloid-rich Phasesmentioning
confidence: 99%
“…[1,125] This would correspond to a range of the attractive depletion well which is in excess of the threshold value (∼σ c /5), below which the colloidal liquid phase is expected to become metastable relative to the solid [124]. However, since the effective polymer packing fraction corresponds to the crossover (or semi-dilute) region between swollen chains and the melt, the range of the depletion interaction is determined not by R g but, rather, by a correlation length ξ , often referred to as the blob size of the polymer [33,[125][126][127]. Using information pertaining to the dimensions of HS polymer chains (see table III of reference [105]) together with a simple scaling argument [105], the blob radius ξ of the 100-segment HS polymer chains at η p = 0.075 can be estimated to be of the order of 3σ m to 4σ m , whereby the range of the interaction would be approximately 6σ m to 8σ m σ c /3 (see Appendix B for a description of the scaling argument).…”
Section: Studies Of the Separate Polymer-rich And Colloid-rich Phasesmentioning
confidence: 99%